Pressure measurements with sensor-equipped Snowboard bindings - Holleczek, T.; Ruegg, A.; Harms, H.; Tröster, G. (Sportinformatik trifft Sporttechnologie. 8. Symposium der dvs-Sektion Sportinformatik in Kooperation mit der Deutschen Interdisziplinären Vereinigung für Sporttechnologie vom 15.-17. September in Darmstadt, 2011)
Snowboarding is one of the fastest growing sports in the world. Requiring complex motion sequences and perfect balance, it is, however, difficult to learn and improving one's snowboarding skills is often only possible through expensive lessons given by an experienced teacher (in Switzerland currently around 100 US$ per hour). Yet even this approach has its limitations, as snowboarding instructors might not notice all mistakes, such as a wrong weight distribution inside the boots. We have therefore been developing a wearable assistant, which is capable of supporting snowboarders in improving their riding style.